THE FALSE NARRATIVE OF SETTLER COLONIALISM PORTRAYED IN ISRAELI CHILDREN’S STORY BOOK - Indah Mustika Santhi (Journal of Language and Literature, 2025)
The false narrative of settler colonialism is a form of colonial narrative through literacy media carried out to be able to control an area and eliminate the identity of the indigenous population of a community. This study aims to dismantle the false narrative contained in one of the Israeli children's story books entitled “Alon and Lebanon". The theoretical basis used in this study is the Critical Discourse Analysis Theory by Teun A. Van Dijk (2001), this theory offers two concepts of analysis levels, namely microlevel analysis and macrolevel analysis. The supporting theories used in this study are Marcel Danesi's Narrative Theory (2004) and Evelyn Nakana Glenn's Settler Colonialism Theory (2014). The study was conducted using qualitative methods. The results of the study show that in the Israeli children's story book entitled “Alon and Lebanon" two types of false narratives were found, namely absurd narrative and deceptive narrative.